The impact of counselling services, employee well-being and workplace behaviour on workplace productivity in debt collection agency in Malaysia - Yasheneedevi, Chandre Segaran (2024)
This study investigates the impact of counselling services, employee well-being, and workplace behaviour on workplace productivity at Titan Recovery Sdn. Bhd., a debt collection agency in Malaysia. The research aims to evaluate how these factors influence productivity and provide actionable recommendations for improving workplace outcomes. Adopting a quantitative approach, the study utilized surveys to gather data from employees of Titan Recovery Sdn. Bhd., with the data analysed using descriptive statistics and regression analysis. The findings indicate that counselling services have a moderate positive relationship with workplace productivity, while employee well-being demonstrates a significant positive impact. Additionally, workplace behaviour exhibits a strong correlation with productivity. These results emphasize the need to prioritize fostering employee well-being and cultivating positive workplace behaviours as critical strategies for enhancing productivity, alongside leveraging counselling services as a supportive resource. This research offers valuable insights into the role of human resource strategies in improving productivity within the debt collection agency. It underscores the importance of promoting employee well-being and constructive workplace behaviours to achieve sustainable organizational success